Kanglaite Combined With Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitor Therapy for Stage III/IV Non-Small Cell Lung Cancer: A PRISMA-Compliant Meta-Analysis - Kong, Fanming; Wang, Chaoran; Li, Xiaojiang; Jia, Yingjie (Frontiers in Pharmacology, 2021)
Objective: Kanglaite(KLT), a type of Chinese medicine preparation, is considered as an adjuvant therapeutic option for malignant cancer treatment. This study aimed to systematically investigate the efficacy and safety of the combination of KLT and epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) for the treatment of stage III/IV non-small cell lung cancer. Methods: Randomized controlled trials (RCTs) that compared KLT plus EGFR-TKI with EGFR-TKI alone for the treatment of stage III/IV non-small cell lung cancer were reviewed. Literature searches (up to July 10, 2021) were performed on PubMed, Web of Science, Cochrane Library, Embase, ClinicalTrials.gov, China National Knowledge Infrastructure (CNKI), Wanfang Database, and the Chinese Scientific Journal Database. Two researchers independently assessed the risk of bias with the tool of Cochrane Collaboration. RevMan 5.3.0 was used in the analysis of the included trial data. Results: 12 RCTs recruiting 1,046 patients with stage III/IV NSCLC were included. Results showed that compared with EGFR-TKI alone, KLT plus EGFR-TKI significantly increased the disease control rate (DCR) (odds ratio [OR]=3.26; 95% confidence interval [CI]:2.22–4.77; p < 0.00001), the objective response rate (ORR) (OR=2.59; 95% CI:1.87–3.58; p < 0.00001) and Karnofsky performance status (KPS) (OR = 2.76; 95% CI:1.73–4.39; p < 0.00001). Furthermore, patient immunity was enhanced with KLT plus EGFR-TKI. The combined treatment increased the percentage of CD4 + T cells (weighted mean difference [WMD]=5.36; 95% CI:3.60–7.13; p < 0.00001),the CD4+/CD8 + ratio (WMD = 0.18; 95% CI: 0.08–0.27; p = 0.004), and percentage of NK cells (WMD=4.84; 95% CI: 3.66–6.02; p < 0.00001).With regard to drug toxicity, the occurrence rate of nausea and vomiting was significantly reduced by KLT plus EGFR-TKI (OR=0.37; 95% CI: 0.16–0.86; p = 0.02). Conclusion: KLT plus EGFR-TKI was effective in treating stage III/IV non-small cell lung cancer. Thus, its application in these patients is worth promoting. Additional double-blind, well-designed and multicenter RCTs are required to confirm the efficacy and safety of this treatment.